BLUETOOTH APPLICATION FOR TEMPERATURE AND HUMIDITY CONTROL - Emil Gocan; Gabriela Bucur (Romanian Journal of Petroleum & Gas Technology, 2023)
The paper presents an application that involves the real-time acquisition of two quantities: humidity and temperature; displaying them on a high-resolution OLED screen; activation of a cooling fan when the set temperature value is exceeded; the possibility of setting the reference temperature value through the Android/iOS mobile application, which communicates with the installation via Bluetooth. To create the application, programming algorithms are used that read these quantities in real time using the DTH 11 sensor, an Arduino Uno development board equipped with the Atmega328 microcontroller, using digital and analog pins. Information is displayed on a high-resolution colour OLED screen attached to the Arduino board. From the created mobile Android application, the temperature value to be compared can be set and an LED for ON/OFF status can be ordered.